Turbulent and Laminar Regime of Liquid Movement - Xolbekov Toshturdi Qudratovich; Jalilov Nuriddin Rahmonovich; Shamsiddin Sayfuddinov Aliasqar o’g’li (Genius Publishing Group, 2022)
This article describes the turbulent and laminar modes of hydrodynamic fluid motion, the effects on solids and liquids, and the effects of minimal tangential forces.
Keywords: Hydrodynamics; laminar; turbulent; matter